Fusarium sacchari, a cause of mycotic keratitis among sugarcane farmers – a series of four cases from North India. Issue 11 (November 2016) - Bansal, Yashik; Chander, Jagdish; Kaistha, Neelam; Singla, Nidhi; Sood, Sunandan; van Diepeningen, Anne D.
Summary: The two most common filamentous fungi causing mycotic keratitis are Aspergillus and Fusarium spp. Around 70 Fusarium spp. are involved in causing human infections. In this study, four cases of keratitis in sugarcane farmers in India are being reported, caused by the sugar cane pathogen Fusarium sacchari, a species of the Fusarium fujikuroi species complex. Fusarial keratitis was established by potassium hydroxide/Calcofluor white wet mounts and fungal culture of corneal scrapings on conventional media. Final identification was done by genetic sequencing at CBS‐KNAW, Utrecht, The Netherlands. The antifungal susceptibility testing was done using broth microdilution method as per CLSI document M38‐A2. Four cases of F. sacchari keratitis were identified. Three of them had trauma with sugarcane leaves, whereas one sugarcane farmer reported trauma by vegetative matter. The morphological similarities among various Fusarium species warrant use of molecular methods for identification of cryptic species. A wide distribution of sugarcane farming could be the possible explanation for emergence of F. sacchari keratitis in India.